Adenoıds And Head Posture - Yahya Tosun; Şafak Tezcan; Halil İbrahim Erol (Galenos Yayinevi, 1992)
Adenoids, hipertrophied by various reasons can obstract the nasopharyngeal airway partially or completely during childhood, causing changes in the individual's breathing pattern. Close correlations among breathing pattern, head posture and craniofacial morphology is known. Clinically, nasopharyngeal airway dimensions can be measured practically and reliably by means of lateral cephalometric films. It is shown that, this method is also in correlation with rhinomanometric measurement methods. It is frequently suggested to have frankfurt Horizontal plane parallel to the floor while taking cephalometric films and orthodontic photographs. The purpose of this study was to determine the head posture and FH plane inclination in the subjects with adenoidectomy indication and to compare the resulst with those of the control subjects.